The state of water use at car washes in some cities of Kazakhstan - Saginov, Адильгерей (Рroblems of engineering and professional education, 2023)
After the stabilization of the Kazakh economy, the rapid industrial and economic growth of our state has continued since the 2000 y. Economic development was accompanied by an increase in the standard of living of citizens of Kazakhstan, which led to an increase in the number of car owners, and the demand for car repair facilities is also growing. These circumstances urge us to increase the number of car washes / car washes in our cities and towns, meanwhile, on the other hand, all this is duplicated by a significant increase in loads on the network and sewage treatment facilities of the water supply and sewage systems, and the classic technologies of circulating water left over from the times of the USSR, Lost their relevance